Archaeology cities, empires, religion, migrations of the past. (Australia National Geographic Learning, 2014)
Brings together investigations into the past and highlights how recent research is revolutionizing our understanding of human history
The pyramid builders -- The birth of religion -- Beyond the blue horizon -- Lofty ambitions of the Inca -- Divining Angkor.
Keywords: Archaeology